Effects of tall alleles SD1-in and SD1-ja to the dwarfing allele sd1-d originating from 'Dee-geo-woo-gen' on yield and related traits on the genetic background of indica IR36 in rice - Rana, Birendra Bahadur (Breeding science, 2021)
Copyright © 2021 by JAPANESE SOCIETY OF BREEDING.